2019
DOI: 10.1098/rstb.2019.0156
|View full text |Cite
|
Sign up to set email alerts
|

The role of motile cilia in the development and physiology of the nervous system

Abstract: Motile cilia are miniature, whip-like organelles whose beating generates a directional fluid flow. The flow generated by ciliated epithelia is a subject of great interest, as defective ciliary motility results in severe human diseases called motile ciliopathies. Despite the abundance of motile cilia in diverse organs including the nervous system, their role in organ development and homeostasis remains poorly understood. Recently, much progress has been made regarding the identity of motile ciliated cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 175 publications
(344 reference statements)
0
81
0
Order By: Relevance
“…The cilium of progenitors is in direct contact with CSF, which provides the niche and growth factors necessary for the stem cells to retain their stemness (Fame & Lehtinen, 2020; Lehtinen et al, 2011; Silva‐Vargas et al, 2016). Interestingly, Kishimoto et al observed that the cilia of radial glia on the adult telencephalic wall have a 9 + 2 microtubule organization (Kishimoto et al, 2011), which is mostly observed in motile cilia (Ringers et al, 2020) and suggest that these cilia may be motile. These cells may therefore have flow‐producing properties similar to the motile monociliated cells of the larval zebrafish brain ventricles (Fame, Chang, Hong, Aponte‐Santiago, & Sive, 2016; Olstad et al, 2019; van Leeuwen et al, 2018) and spinal cord (Kramer‐Zucker et al, 2005; Ringers et al, 2020; Sternberg et al, 2018; Thouvenin et al, 2020).…”
Section: Function Of Glia In Brain Homeostasis At the Brain Barriers mentioning
confidence: 99%
See 1 more Smart Citation
“…The cilium of progenitors is in direct contact with CSF, which provides the niche and growth factors necessary for the stem cells to retain their stemness (Fame & Lehtinen, 2020; Lehtinen et al, 2011; Silva‐Vargas et al, 2016). Interestingly, Kishimoto et al observed that the cilia of radial glia on the adult telencephalic wall have a 9 + 2 microtubule organization (Kishimoto et al, 2011), which is mostly observed in motile cilia (Ringers et al, 2020) and suggest that these cilia may be motile. These cells may therefore have flow‐producing properties similar to the motile monociliated cells of the larval zebrafish brain ventricles (Fame, Chang, Hong, Aponte‐Santiago, & Sive, 2016; Olstad et al, 2019; van Leeuwen et al, 2018) and spinal cord (Kramer‐Zucker et al, 2005; Ringers et al, 2020; Sternberg et al, 2018; Thouvenin et al, 2020).…”
Section: Function Of Glia In Brain Homeostasis At the Brain Barriers mentioning
confidence: 99%
“…Interestingly, Kishimoto et al observed that the cilia of radial glia on the adult telencephalic wall have a 9 + 2 microtubule organization (Kishimoto et al, 2011), which is mostly observed in motile cilia (Ringers et al, 2020) and suggest that these cilia may be motile. These cells may therefore have flow‐producing properties similar to the motile monociliated cells of the larval zebrafish brain ventricles (Fame, Chang, Hong, Aponte‐Santiago, & Sive, 2016; Olstad et al, 2019; van Leeuwen et al, 2018) and spinal cord (Kramer‐Zucker et al, 2005; Ringers et al, 2020; Sternberg et al, 2018; Thouvenin et al, 2020). Of note, motile monociliated cells described at larval zebrafish are not radial glia, but instead, they constitute other cell types (Olstad et al, 2019; van Leeuwen et al, 2018).…”
Section: Function Of Glia In Brain Homeostasis At the Brain Barriers mentioning
confidence: 99%
“…CSF flow in the brain ventricles consists of a macrofluidic component, which makes up the bulk of flow in the middle of the ventricles, and a microfluidic component close to the ventricle wall (Ringers et al, 2020;Siyahhan et al, 2014). The major bulk of flow is driven by a number of cues, such as the pressure gradient created by CSF secretion, exchange of CSF with interstitial fluid, cardiac and respiratory cycles, and even body movements, which therefore make CSF flow difficult to study (Dreha-Kulaczewski et al, 2015;Feinberg and Mark, 1987;Olstad et al, 2019;Ringers et al, 2020;Spassky et al, 2005;Xu et al, 2016). The bulk CSF flow is primarily thought to nourish the brain and maintain brain homeostasis (Ringers et al, 2020).…”
Section: Brain Ventricular Systemmentioning
confidence: 99%
“…However, individuals with primary ciliary dyskinesia barely present with hydrocephalus (Lee, 2013), which suggests apparent differences between species. These differences could possibly be explained by the difference in ventricular size, which could change the contribution of bulk CSF flow compared with near-wall CSF flow (Ringers et al, 2020).…”
Section: Brain Ventricular Systemmentioning
confidence: 99%
“…cells in the left-right organizer [1] or in the central canal of the spinal cord [2], or can bear bundles of cilia [3], e.g. cells with ependymal cilia in the brain [4,5] or multi-ciliated cells in the respiratory tract [6]. Motile cilia can also be highly specialized, i.e.…”
Section: Main Body 1 Introductionmentioning
confidence: 99%